A monkey Alu sequence is flanked by 13-base pair direct repeats by an interrupted alpha-satellite DNA sequence. - Grimaldi, G (1982)
A member of the Alu family, the dominant family of short interspersed repeated DNA sequences in primates, interrupts a cloned repeat unit of African green monkey alpha-satellite DNA. The Alu is immediately flanked by 13-base-pair duplications of the known sequence of the satellite at the site of insertion. These observations support the idea that Ala family members may be moveable elements.